Phosphate-doped high-entropy oxide battery negative electrode material, preparation method and application
The preparation of phosphate-doped high-entropy oxide materials and the solution combustion method form a porous mesh structure, which solves the problems of low conductivity and poor Coulomb efficiency of high-entropy oxide negative electrode materials, and achieves a significant improvement in material performance.
Patent Information
- Application Number
- CN202510116861.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
High-entropy oxide negative electrode materials have problems with low intrinsic conductivity and poor Coulomb efficiency.
By preparing phosphate-doped high-entropy oxide materials, a porous mesh structure is formed by solution combustion, and lattice distortion and oxygen vacancies are introduced through doping of metal-like P elements to optimize electron/ion transport efficiency.
It significantly improves the intrinsic conductivity and charge/discharge cycle specific capacity of the material, and improves the first-round Coulomb efficiency and cycle stability.
Smart Images

Figure CN119812314A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy materials, and in particular relates to a phosphate-doped high-entropy oxide battery negative electrode material, a preparation method and an application thereof. Background Art
[0002] In the current booming field of electrochemistry, high entropy oxides (HEOs) are showing a rapid development trend. Compared with traditional transition metal oxides, high entropy oxides based on a unique multi-principal element design have a series of excellent properties. The high entropy effect increases the entropy of the system and forms a stable solid solution phase; the lattice distortion effect increases the defect density, providing more channels and active sites for electron / ion transmission; the slow diffusion effect inhibits the change of electrode structure during battery charging and discharging, and improves the cycle stability; the cocktail effect enables multiple elements to work synergistically to improve the overall performance of the material.
[0003] However, high entropy oxide anode materials have inherent disadvantages such as low intrinsic conductivity and poor rate performance. + The results of the study showed that with the increase of Li + With the gradual increase of the content, the oxygen vacancy concentration in the material increases, which in turn improves the electronic conductivity (Maciej Mozdzierz, Juliusz Dabrowa, Anna Stepie, et al. Mixed ionic-electronic transport in the high-entropy (Co, Cu, Mg, Ni, Zn) 1-x Li x O oxides. Acta Materialia, 2021, 208: 116735.). Justin and his team of researchers conducted research on alkali metal Na-doped high entropy oxides and found that the grain boundary structure has a very significant effect on the conductivity. By adjusting the Na content, the conductivity of the material can be effectively improved (Justin Cortez, Alexander Dupuy, Hasti Vahidi, et al. Tunable grain boundary conductivity insodium doped high entropy oxides. Solid State Ionics, 2025, 419: 116745.). In addition, researchers often use inactive transition metal cations doping (such as alkali metal cations Li + 、Na + , K + and Al 3+ Elements such as lattice distortion and oxygen vacancies can be used to control defects such as lattice distortion and oxygen vacancies, but metal-like P5+ Element doping has rarely been reported. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of current high entropy oxide negative electrode materials such as low intrinsic conductivity and poor Coulomb efficiency, and to provide a phosphate-doped high entropy oxide battery negative electrode material, a preparation method and an application thereof.
[0005] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:
[0006] The present invention provides a phosphate-doped high entropy oxide secondary battery negative electrode material, the chemical formula of which is (M 1-x P x )3O4, wherein x=0.05~0.1, and M is at least five of Mg, Cr, Mn, Co, Fe, Ni, and Zn; the material has a hollow network morphology.
[0007] The present invention also provides a method for preparing a phosphate-doped high entropy oxide secondary battery negative electrode material, comprising the following steps:
[0008] 1) According to the chemical formula (M 1-x P x )3O4 weigh a stoichiometric ratio of metal salt and phosphate, dissolve them in distilled water, stir evenly, and obtain a mixed salt solution of metal salt and phosphate;
[0009] 2) Weighing a certain amount of glycine as a fuel, adding it to the mixed salt solution obtained in step 1), stirring it evenly at room temperature, and then placing it in an oven to evaporate the water therein to obtain a mixed gel;
[0010] 3) placing the mixed gel obtained in step 2) into a transparent electric furnace for solid phase reaction, and obtaining a phosphorus-doped single-phase high entropy oxide after air cooling.
[0011] Furthermore, in step 1), the metal salt is a nitrate or a partially soluble dihydrogen phosphate.
[0012] Furthermore, in step 1), the phosphate is diammonium phosphate or diammonium hydrogen phosphate.
[0013] Furthermore, in step 2), the temperature of the oven is controlled at 80-100°C.
[0014] Furthermore, in step 2), the molar ratio of the fuel to the total cations in the mixed salt solution is 0.26 to 1.46:1.
[0015] Furthermore, in step 3), the temperature of the solid phase reaction is controlled at 300-950° C., and the reaction time is controlled at 2-30 min.
[0016] The present invention also provides an application of a phosphate-doped high entropy oxide secondary battery negative electrode material in preparing a secondary battery negative electrode material.
[0017] The beneficial effects of the present invention are:
[0018] 1. Use solution combustion method to ensure that all raw materials are evenly mixed at the molecular scale. At the same time, the microstructure of the material is regulated to form a porous network structure.
[0019] 2. By doping with metal-like P elements, defect engineering such as lattice distortion and oxygen vacancies is introduced to further improve the electron / ion transmission efficiency, optimize the intrinsic conductivity, and increase the charge / discharge cycle specific capacity.
[0020] 3. Under oxygen-deficient conditions, glycine is used as fuel, and a rapid reaction is achieved by controlling the amount of fuel used to synthesize spinel high-entropy oxides with lattice distortion and abundant oxygen vacancies.
[0021] 4. The preparation process of the present invention is simple, the reaction conditions are mild, no complicated equipment and cumbersome operations are required, green and environmentally friendly raw materials are used in the preparation process, no harmful by-products are produced, and it is in line with the concept of sustainable development.
[0022] Of course, any product implementing the present invention does not necessarily need to achieve all of the above advantages at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0024] Figure 1 A phosphate-doped spinel (Co 0.19 Fe 0.19 Mn 0.19 Ni 0.19 Zn 0.1 9P 0.05 )XRD pattern of 3O4 high entropy oxide;
[0025] Figure 2 A phosphate-doped spinel (Co 0.19 Fe 0.19 Mn 0.19 Ni 0.19 Zn 0.1 9P 0.05 ) SEM image of 3O4 high entropy oxide at 2,000 times magnification;
[0026] Figure 3 A phosphate-doped spinel (Co 0.19 Fe 0.19 Mn 0.19 Ni 0.19 Zn 0.1 9P 0.05 ) SEM image of 3O4 high entropy oxide at 5,000 times magnification;
[0027] Figure 4 A phosphate-doped spinel (Co 0.19 Fe 0.19 Mn 0.19 Ni 0.19 Zn 0.1 9P 0.05 )SEM image of 3O4 high entropy oxide at 20,000 times;
[0028] Figure 5 A phosphate-doped spinel (Co 0.19 Fe 0.19 Mn 0.19 Ni 0.19 Zn 0.1 9P 0.05 )Intrinsic conductivity diagram of 3O4 high entropy oxide;
[0029] Figure 6 A phosphate-doped spinel (Co 0.19 Fe 0.19 Mn 0.19 Ni 0.19 Zn 0.1 9P 0.05 )Schematic diagram of the cycling performance of 3O4 high entropy oxide negative electrode material at a current density of 200mA / g. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The present invention selects metal nitrate as a metal source, uses glycine as a fuel, and adds ammonium dihydrogen phosphate as a source of metal-like phosphorus. By precisely controlling the concentrations of metal nitrate and ammonium dihydrogen phosphate, a phosphate-doped spinel type (M 1-x P x)3O4 high entropy oxide secondary battery negative electrode material.
[0032] The specific embodiments of the present invention are as follows:
[0033] Example 1
[0034] Preparation of a phosphate-doped spinel high entropy oxide negative electrode material:
[0035] According to the molecular formula (Co 0.19 Fe 0.19 Mn 0.19 Ni 0.19 Zn 0.19 P 0.05 )3O4 in a stoichiometric ratio, specifically: accurately weigh 1.1875 mmol of equimolar metal nitrates (Co(NO3)2·6H2O, Fe(NO3)3·9H2O, Mn(NO3)2·4H2O, Ni(NO3)2·6H2O and Zn(NO3)2·6H2O) and 0.3125 mmol of diammonium phosphate (NH4H2PO4), add 4.06 mmol of fuel glycine, stir evenly at room temperature, and obtain a mixed salt solution containing metal nitrates and phosphates;
[0036] Then, the mixed salt solution was poured into a porcelain boat and placed in an oven at 80°C to evaporate the water to obtain a gel precursor. The solid phase reaction was carried out at 750°C in a transparent electric furnace for 30 minutes. After cooling to room temperature, the mixture was washed with distilled water and ethanol three times each. After drying, a single spinel structure (Co 0.19 Fe 0.19 Mn 0.19 Ni 0.19 Zn 0.19 P 0.05 )3O4 high entropy oxide negative electrode material;
[0037] The XRD spectrum of the powder material ( Figure 1 ) shows that the prepared (Co 0.19 Fe 0.19 Mn 0.19 Ni 0.19 Zn 0.19 P 0.05 )3O4 high entropy oxide has a single spinel structure. SEM ( Figure 2-Figure 4 ) confirmed that the prepared high entropy oxide has a porous structure and the distribution of each element is uniform. Four-probe conductivity ( Figure 5 ) The test results show that the electrical conductivity of high entropy oxide increased by nearly 3 times after metal-like P doping.
[0038] Preparation of working electrode and assembly of lithium-ion battery:
[0039] The prepared sample was used as the active material, Super P carbon black as the conductive agent, and sodium alginate as the binder (mass ratio 7:2:1), ground into a slurry in a mortar and evenly coated on a neat copper foil to make an electrode sheet; then a pure lithium sheet was used as the positive electrode, a polypropylene porous membrane was used as the separator, and a solution of 1 mol / L LiPF6 in DMC-EC-DEC (volume ratio 1:1:1) was used as the electrolyte to assemble into a CR2025 button cell in a glove box.
[0040] The battery charging and discharging experiment was carried out on the Xinwei battery testing system. The results are as follows: Figure 6 As shown: (Co 0.19 Fe 0.19 Mn 0.19 Ni 0.19 Zn 0.19 P 0.05 )3O4 electrode was tested for charge and discharge cycles at a current density of 200mA / g. Within the voltage range of 0.01-3.0V, the specific capacity after 30 cycles was 596.4mAh / g, the first cycle coulomb efficiency was 77.2%, and the capacity retention rate was 85.7%. The results show that the lattice distortion and oxygen vacancies introduced by metal-like phosphorus doping improve the first cycle coulomb efficiency of the electrode ((Co 0.2 Fe 0.2 Mn 0.2 Ni 0.2 Zn 0.2 )3O4 is 71.2%), and the early cycle stability is relatively excellent. Compared with the charge / discharge specific capacity of the electrode during the first cycle, the capacity retention rate is still close to 90%.
[0041] Example 2
[0042] Preparation of a phosphate-doped spinel high entropy oxide negative electrode material:
[0043] According to the molecular formula (Co 0.19 Fe 0.19 Mn 0.19 Ni 0.19 Zn 0.19 P 0.05 )3O4, the corresponding metal nitrates and phosphates are weighed in a stoichiometric ratio, specifically: accurately weigh 1 mmol of equimolar metal nitrates (Co(NO3)2·6H2O, Fe(NO3)3·9H2O, Mn(NO3)2·4H2O, Ni(NO3)2·6H2O and Zn(NO3)2·6H2O), and 0.3125 mmol of diammonium hydrogen phosphate ((NH4)2HPO4), add 4.06 mmol of fuel glycine, stir evenly at room temperature, and obtain a mixed salt solution containing metal nitrates and phosphates;
[0044] Then, the mixed salt solution was poured into a porcelain boat and placed in an oven at 80°C to evaporate the water to obtain a gel precursor. The solid phase reaction was carried out at 750°C in a transparent electric furnace for 30 minutes. After cooling to room temperature, the mixture was washed with distilled water and ethanol three times each. After drying, a single spinel structure (Co 0.17 Fe 0.17 Mn 0.17 Ni 0.17 Zn 0.17 P 0.15 )3O4 high entropy oxide negative electrode material.
[0045] Example 3
[0046] Preparation of a phosphate-doped spinel high entropy oxide negative electrode material:
[0047] According to the molecular formula (Co 0.18 Fe 0.18 Mn 0.18 Ni 0.18 Zn 0.18 P 0.1 )3O4 in a stoichiometric ratio, specifically: accurately weigh 1.125 mmol of equimolar metal nitrates (Co(NO3)2·6H2O, Fe(NO3)3·9H2O, Mn(NO3)2·4H2O, Ni(NO3)2·6H2O and Zn(NO3)2·6H2O) and 0.625 mmol of diammonium phosphate (NH4H2PO4), add 4.31 mmol of fuel glycine, stir evenly at room temperature, and obtain a mixed salt solution containing metal nitrates and phosphates;
[0048] Then, the mixed salt solution was poured into a porcelain boat and placed in an oven at 80°C to evaporate the water to obtain a gel precursor. The solid phase reaction was carried out at 750°C in a transparent electric furnace for 30 minutes. After cooling to room temperature, the mixture was washed with distilled water and ethanol three times each. After drying, a single spinel structure (Co 0.18 Fe 0.18 Mn 0.18 Ni 0.18 Zn 0.18 P 0.1 )3O4 high entropy oxide negative electrode material;
[0049] Example 4
[0050] Preparation of a phosphate-doped spinel high entropy oxide negative electrode material:
[0051] According to the molecular formula (Co 0.18 Fe 0.18 Mn 0.18 Ni0.18 Zn 0.18 P 0.1 )3O4, the corresponding metal nitrates and phosphates are weighed in a stoichiometric ratio, specifically: accurately weigh 1.125mmol of equimolar metal nitrates (Co(NO3)2·6H2O, Fe(NO3)3·9H2O, Mn(NO3)2·4H2O and Ni(NO3)2·6H2O), and at the same time weigh 0.8125mmol of a mixed salt solution of Zn(NO3)2·6H2O and 0.3125mmol of Zn(H2PO4)2 as a zinc source and a phosphorus source, add 4.31mmol of fuel glycine, and stir evenly at room temperature to obtain a mixed salt solution containing metal nitrates and phosphates;
[0052] Then, the mixed salt solution was poured into a porcelain boat and placed in an oven at 80°C to evaporate the water to obtain a gel precursor. The solid phase reaction was carried out at 750°C in a transparent electric furnace for 30 minutes. After cooling to room temperature, the mixture was washed with distilled water and ethanol three times each. After drying, a single spinel structure (Co 0.18 Fe 0.18 Mn 0.18 Ni 0.18 Zn 0.18 P 0.1 )3O4 high entropy oxide negative electrode material.
[0053] The present invention provides a phosphate-doped spinel high entropy oxide negative electrode material and its preparation method and application, aiming to effectively solve the key problems of the high entropy oxide negative electrode material such as low intrinsic conductivity and poor first-cycle coulomb efficiency. The chemical formula of the material is (M 1-x P x )3O4, wherein x ranges from 0.05 to 0.1, and M is at least five elements selected from Mg, Cr, Mn, Co, Fe, Ni, and Zn. The present invention adopts a solution combustion method, which can not only form a porous network structure, but also regulate defects such as oxygen vacancies and lattice distortion under oxygen-deficient conditions by element regulation and precise control of the amount of fuel glycine; at the same time, by means of doping with metalloid P elements, defects such as lattice distortion and oxygen vacancies are introduced, which effectively enhances the transmission efficiency of electrons / ions, optimizes and improves the intrinsic conductivity of the material, and further improves the first-cycle coulomb efficiency and specific capacity during the battery charge / discharge cycle. The entire preparation process has the outstanding advantages of simplicity and efficiency, relatively mild reaction conditions, and green and environmentally friendly raw materials.
[0054] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A phosphate-doped high entropy oxide secondary battery negative electrode material, characterized in that: The chemical formula of this material is (M 1-x P x )3O4, wherein x=0.05~0.1, and M is at least five of Mg, Cr, Mn, Co, Fe, Ni, and Zn; the material has a hollow network morphology.
2. The method for preparing a phosphate-doped high entropy oxide secondary battery negative electrode material according to claim 1, characterized in that: The steps include: 1) According to the chemical formula (M 1-x P x )3O4 weigh a stoichiometric ratio of metal salt and phosphate, dissolve them in distilled water, stir evenly, and obtain a mixed salt solution of metal salt and phosphate; 2) Weighing a certain amount of glycine as a fuel, adding it to the mixed salt solution obtained in step 1), stirring it evenly at room temperature, and then placing it in an oven to evaporate the water therein to obtain a mixed gel; 3) placing the mixed gel obtained in step 2) into a transparent electric furnace for solid phase reaction, and obtaining a phosphorus-doped single-phase high entropy oxide after air cooling.
3. The preparation method according to claim 2, characterized in that: In step 1), the metal salt is a nitrate or a partially soluble dihydrogen phosphate.
4. The preparation method according to claim 2, characterized in that: In step 1), the phosphate is ammonium dihydrogen phosphate or diammonium hydrogen phosphate.
5. The preparation method according to claim 2, characterized in that: In step 2), the temperature of the oven is controlled at 80-100°C.
6. The preparation method according to claim 2, characterized in that: In step 2), the molar ratio of the fuel to the total cations in the mixed salt solution is 0.26-1.46:
1.
7. The preparation method according to claim 2, characterized in that: In step 3), the temperature of the solid phase reaction is controlled at 300-950° C., and the reaction time is controlled at 2-30 min.
8. Use of the phosphate-doped high entropy oxide secondary battery negative electrode material as claimed in claim 1 in preparing secondary battery negative electrode materials.
Citation Information
Patent Citations
High-entropy oxide OER electrocatalyst and preparation method and application thereof
CN118422265A
Methods for reducing magnetic and / or oxidic impurities in lithium-metal-oxygen compounds
DE102010032207A1